The contextual determinants of risky behaviours among adolescent in South Africa - Mazonde, Tania Gamuchirayi (My University, 2017)
Background: Risky behaviours among adolescents are notably the most important factors contributing to negative health outcomes of this population group. Adolescents in South Africa are at risk of the HIV infection, unintended pregnancies, unintentional injuries (motor vehicle accidents) and substance and drug abuse. South Africa is regarded as one of the countries with nearly half adolescents living with HIV, as a result of unprotected sex. It is also regarded as one of the countries with motor accidents cases and as a result of reckless driving and substance use. To understand this, there is substantial research on the demographic and socio-demographic determinants of risky behaviour amongst adolescents but little research on the household and community factors. The main aim of this study is to determine the contextual determinants of adolescent risky behaviours in South Africa. Method: This study used data from the South African Youth Life Style Survey of 2008. The study sample size is 3336 adolescents aged 12 to 19 across all nine provinces in South Africa. Risky behaviours are organized using an ecological framework into individual, household, and community levels. Binary- multilevel logistic regression was employed to analyze the data. Results: The results indicated that age, sex, education, race, living arrangements, number of income earners, were significant, however, the relationship between risky behaviours and community level variables were negatively significant. . 3336 adolescents participated in the study, 934 (28.0%) had sexual intercourse and 158 (4.74%) had two or more sexual partners, and 234 (7.01) did not use a condom during their last sex. In terms of substance use, 34.24 % ever used alcohol and about 24.45% ever been a passenger with a driver under the influence. Adolescents who were living with their grandparents (OR=1.07), living in a household with seven or more members (OR=1.06), while residing in had a higher likelihood of engaging in risky behaviours. Findings demonstrated that community level factors were not associated with reports of risky behaviour among adolescents but were influential in shaping the risky behaviour of adolescents. Conclusion: Firstly, results from this research will provide a better understanding of the contextual factors that relate to risky behaviours. Secondly, results from this research will help inform polices such as the National Youth Policy in reducing risky behaviours. Lastly, interventions aimed at reducing risky behaviours among adolescents in South Africa should not only focus on individual level but also on the household and community engagement.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the award of Masters of Arts in Demography and Population Studies, 2017
Keywords: Risk-taking (Psychology)--South Africa; Teenagers--Drug use--South Africa; Teenagers--Sexual behaviour--South Africa; Teenage pregnancy--South Africa; Sexually transmitted diseases--South Africa.